Content Analysis of Recordkeeping Job Advertisements in Western Australia: Knowledge and Skills Required by Employers - Pember, Margaret (2003)
Since professional education for recordkeeping first commenced the nature of the profession has changed considerably and courses have undergone a number of metamorphoses. One of the major drivers for course change should be industry need. A content analysis of a sample of Western Australian recordkeeping job advertisements way conducted to identify the specific knowledge and skills in demand by employers. From an analysis of the positions advertised it is clear that employers expect recordkeeping professionals to possess a diverse range of recordkeeping knowledge and experience, ranging from basic entry-level hands-on processing skills to high level strategic planning skills. Often positions require knowledge and experience in more than one area of information management, for example, recordkeeping and librarianship or recordkeeping and freedom of information. The preferred recordkeeping professional will also be proficient in transferable employment competencies such as a high level of computer literacy, well developed communication and interpersonal skills, staff management skills and experience, well developed teaming skills, and a strong customer focus. Personal attributes such as enthusiasm, motivation, and analytical and problem solving skills were also considered of great importance. Over one-third of the advertisements indicated that a tertiary qualification or progress towards a tertiary qualification was required as either an essential or a desirable criterion, but only 10% mentioned membership of a relevant professional association.